Carte des Iles South-Orkney, Sandwich, Géorgie et d'une partie des terres australes / dressée par Mr. Vincendon-Dumoulin, ingénieur hydrographe de la marine, 1847 - France. Service hydrographique de la marine (1933)
Edition d'Octobre 1930. Corr. . 1933 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange.; Includes 2 pasteovers Grayscale; 1:2,397,000